Legislasi Presidential Impeachment: Komparasi, Status Quo, dan Urgensinya dalam Undang-Undang Lembaga Kepresidenan - Muhammad RM Fayasy Failaq; Erland Ferdinansyah; Umi Zakia Azzahro; Enika Maya Oktavia (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Legislation of the presidential institution has been proposed since 2001 through the draft of the Presidential Institution Law. The problem is that presidential impeachment as a mechanism for limiting presidential power is not regulated. This study aims to: First, compare the regulations on presidential impeachment and impeachment in countries. Second, examine the existence of regulations on presidential impeachment and impeachment that currently exist in Indonesia. Third, measure the urgency of carrying out legislation on presidential impeachment in the Presidential Institution Law. This study is a doctrinal legal study that conducts a literature study with a comparative, conceptual, and legislative approach. The results of this study indicate that based on the comparison there are variations in the regulation of presidential impeachment in countries. Still, starting from the important situation of regulating this in both the constitution and legislative products, the regulation of impeachment in Indonesia itself is spread among many laws and regulations which in some cases causes technical problems in resolving the impeachment mechanism. Therefore, it is necessary to codify impeachment in one Presidential Institution Law.